OPTIMALISASI PERAN GURU DALAM MENDIDIK KARAKTER SISWA MELALUI MEDIA TEMBANG MACAPAT PANGKUR PUPUH 3SERAT WEDHATAMA - Winarto Winarto; Sarafuddin Sarafuddin; BelaVista Dian Devika (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
This community service aims to (1) instill self-confidence to grow development and introduce children to the basic schools to love more and more ancestral culture based on local wisdom; (2) Promote a sense of trust with mental education with good character, based on the development guidelines of Pangkur Pupuh 3Serhatama Fiber, and (3) Fostering a smart and quality society, through basic education that has the spirit of Pancasila. The method of implementation used in this service with learning and training socialization papers. The population of this study were 20 teachers, prospective teachers and students of SDN 3 Suruh. The result of this community service is that the teacher can understand the songs and practice the PangkurPupuh 3SeratWedhatama song. Thus, the method of learning through training and socialization is more effective in making teachers, prospective teachers and students understand the philosophy of Armageddon 3Swedhatama fiber.